Immigration as a traumatic experience, in the stories of immigrants’ daughters - Prisco, Giada; Silva, Clara (Rivista Italiana di Educazione Familiare, 2020)
The paper intends to analyze the processes underlying identity building in girls with a migration background: namely, those subjects in which the adolescent period intertwines with the migration experience, and with the process of identity building. In fact, the construction of identity in immigrant youth is more complex, because the “identity crisis” overlaps with the “trauma” of the experience of migration. This paper aims to investigate how a traumatic situation, such as a migratory experience, may affect the mechanisms of identity building in adolescence. The essay summarizes the outcomes of a qualitative research conducted with a sample of 15 adolescent girls, daughters of im- migrants, aged 15-20, living in Florence and Madrid, in an interdisciplinary perspective, using Grounded Theory as a method of investigation, and a semi-structured interview as a data collection tool. Respondents reported that their situation is doubly complex, due to their status as “migrants” and as adolescents, and as women as well. In fact, especially for girls, the change caused by migration is gender-generating: it therefore leads to the development of new forms of “being women”, differentiating both from the dominant models of the culture of origin, and from those of the immigration country.